Assessment of Quality of life for Patients with Myocardial Infarction - Yass K. Abbas (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To identify quality of life (QOL) in Myocardial Infarction (MI) patients, and to find out the relationship between QOL in MI patients and demographic characteristics. Methodology: A descriptive colTelation study which utilized an assessment approach. The study was carried out from March 2007 through November 2007 in order to assess the quality of life for patients with myocardial infarction. A purposive "non-probability" sample of (75) patients with myocardial infarction who were attending to Baquba General Hospita`l through their visits to that hospital. A questionnaire was adapted and developed from the World Health Organization Quality of Life Scale (1998). The questionnaire was designed and consisted of (2) parts, the fust part includes demographic characteristics of Myocardial Infarction patients, clinical characteristics of these patients and medical sheet information. The second one consists of six domains of quality of life. Reliability was determined by using test and retest technique through a Pilot study. Data were analyzed through descriptive data analysis approach (Frequency and percentage) and the inferential data analysis approach (Pearson con.elation coefficient and chi-square). Results: The results of the study indicated that (53.3%) of the sample was male and (41.7%), age between (61- 70) years, (68.0%) was married and more than two third of sample were unable to read and write, (44%) of the sample was housewife (do not work). The findings of the study present that the demographic characteristics of MI patients such as gender, level of education had a significant relationship with their quality of life. The socioeconomjc characteristics of patients such as marital status hnd no significant relationship with the patients’ quality of life. The finding also shows disease had moderate, low and no effect on quality of life through the relative sufficiency from the spiritual domain (RS=83.8), the independence (RS=76.9), psychological domain (RS=76.7), physical domain (RS=74.6), social domain a`S=69.9), and environment domain (RS=62.3). Recommendations: The study recommended that an educational program for MI patients to help them have a better QOL and advice them how to cope with their problems for a good QOL.